The Livestock Sector in Colombia: Toward a Program to Facilitate Large-Scale Adoption of Mitigation and Adaptation Practices - Tapasco, Jeimar; LeCoq, Jean Fraçois; Ruden, Alejandro; Rivas, Juan Sebastián; Ortiz, Javier (Frontiers in Sustainable Food Systems, 2019)
Livestock raising is a very important sector in the Colombian economy; however, in the next decade, it will face some enormous challenges, including adaptation to and mitigation of climate change. Colombia must change drastically, and in a very short time, the model of livestock production, freeing up areas of pasture for other uses and intensifying livestock production in suitable zones. In spite of the urgency and the magnitude of the required changes, only isolated small-scale initiatives exist. Thus, Colombia has the challenge of the scaling up of measures, but, up to now, it has had no program designed to achieve this. Starting from an analysis of the policies, actors, and existing initiatives, we seek to understand the potentialities for and limitations to the scaling up of promising practices to face the challenges of climate change in the livestock sector in Colombia. We show the elements that have been key in previous initiatives regarding the spaces for scaling up: policy space, fiscal and financial space, institutional capacity space, learning space, partnership space, technical space, and other spaces, to which we add the importance of the technical dimension. Finally, we propose some elements for designing a national program of reconversion of livestock raising for the Colombian context.